Root and shoot growth of soybean (Glycine max) as influenced by naturally available phosphorus nutrition with manure - Sithamparam, Piraveena; Seran, Thayamini H (Journal of Agriculture and Environment, 2014)
Effect of rock phosphate (RP) combined with cattle manure (CM) on plant growth of soybean was studied. As basal fertilizer application, RP at different levels (0, 25, 50, 75 and 100 kg/ha) along with 10 tons/ha CM (T2-T6) were applied and also recommended chemical fertilizer (T1 as a control). The results revealed that seed-pod ratio ranged from 0.68 to 0.74 at the maturity stage (12 weeks) and the highest ratio (0.74) was reported in RP (50 kg/ha) with CM (T4) and lowest value (0.68) was observed when CM solely applied. Further, the plants grown in inorganic fertilizer had a high root-shoot ratio (1:17) while comparatively lower ratios (1:12 to 1:15) were noted in plants grown with RP (0-100 kg/ha) and CM. Application of CM alone or in combination with RP at the optimal level could improve root and shoot growth for better yield of the soybean with less environmental pollution.